2013
DOI: 10.1073/pnas.1217178110
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity and wrinkled morphology of Bacillus subtilis pellicles

Abstract: Wrinkled morphology is a distinctive phenotype observed in mature biofilms produced by a great number of bacteria. Here we study the formation of macroscopic structures (wrinkles and folds) observed during the maturation of Bacillus subtilis pellicles in relation to their mechanical response. We show how the mechanical buckling instability can explain their formation. By performing simple tests, we highlight the role of confining geometry and growth in determining the symmetry of wrinkles. We also experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 31 publications
9
127
0
3
Order By: Relevance
“…Experimental results have shown that during development, wildtype B. subtilis biofilms initially grow in height until reaching a critical thickness at which point vertical growth slows in lieu of horizontal expansion [29,37]. It is also commonly observed that patterning occurs in mature (deep) biofilms [1,5,33]. Thus our analysis is in accordance with observed biological results.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Experimental results have shown that during development, wildtype B. subtilis biofilms initially grow in height until reaching a critical thickness at which point vertical growth slows in lieu of horizontal expansion [29,37]. It is also commonly observed that patterning occurs in mature (deep) biofilms [1,5,33]. Thus our analysis is in accordance with observed biological results.…”
Section: Discussionsupporting
confidence: 82%
“…Biofilm models incorporating additional biological (in particular the role of EPS [18]) and mechanical processes, following similar approaches as explored in e.g. [15,33], may provide a complementary understanding of biofilm pattern formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a standard force sensor in such experiments can reveal the value of the tension [as has been done, for example, with bacterial biofilms, where such force sensors determined that biofilms are under compression rather than tension (Trejo et al, 2013)]. Cutting tissues with a scalpel is obviously only feasible at the macro scale; at smaller scales, lasers can be used.…”
Section: Laser Ablationmentioning
confidence: 99%